Injury alters sensory, motor, and integrative elements underlying operant conditioning in the medicinal leech - Ella R. Dockendorf; Brian D. Burrell (PLoS ONE, 2025)
Studies of pain/nociception often rely on simple reflexes to assess pain-related changes in behavior. However, there is considerable interest in utilizing more complex, self-initiated behaviors in place of stimulus-evoked reflexes. In this study we report an operant conditioning assay using Hirudo verbana (the medicinal leech) to assess the effects of injury on motivational and cognitive processes. Animals were placed in an arena consisting of an illuminated and a dark chamber with a connecting section in between. The connecting section was partially filled with gravel, which acted as an obstacle and delayed escape from the illuminated to the dark side. With repeated experience H. verbana learned to overcome the gravel obstacle, reflected as a decreased escape latency from the illuminated chamber. The capacity for this enhanced escape behavior was retained for up to two hours. In animals that received an injury to the posterior sucker, learning and memory of this operant escape task was disrupted. Injured animals also exhibited mechanosensory sensitization, changes in locomotion, changes in exploratory behavior, and increased negative phototaxis. Over 12 days, changes in locomotion, exploratory behavior, and phototaxis recovered to pre-injury levels, although mechanosensory sensitization remained. Disruptions in cognitive behavior also recovered during this period with the capacity for operant conditioning returning six days after injury and two hour retention of conditioning returning by day 12. This study shows that injury produces a complex and coordinated set of sensory, motor, and integrative changes in H. verbana that may be relevant to understanding the biological processes behind pain in vertebrates.